ST2 Levels Before and After Treatment of NYHA III and IV Heart Failure - Suzanna Immanuel; Neila Mona AG Mandey; Lukman H Makmun (Interna Publishing, 2015)
Aim: to find whether ST2 can be used to determine clinical improvement in patients with NYHA III and IV heart failure. Methods: this is a longitudinal, pre and post-test study without a control group. Study subjects are 23 NYHA III and IV heart failure patients. ST2 was tested at the start and end of hospital treatment. Results: of 23 heart failure patients, 70% were classified as NYHA III while 30% were NYHA IV. There were more male subjects than females (51.4% vs. 48.6%). Median age for NYHA III heart failure patients was 52 years and mean age for NYHA IV heart failure patients was 58 years. Heart failure was mostly caused by coronary artery disease (52%). ST2 levels did not correlate with age, length of care, sex and cause of heart failure. ST2 levels in NYHA IV heart failure patients (58.82±37.36 ng/mL) tended to be higher than the one in NYHA III group (30.75 [14.4-84.5] ng/mL), but the difference was statistically not insignificant (p=0.89). ST2 levels at the start of treatment was significantly higher than at the end (31.4 [14-129.2] ng/mL vs. 18.4 [7.6-77.8] ng/mL), p=0.001. This shows that clinical improvement is associated with significant reduction of ST2 levels. Conclusion: ST2 can be used as a marker to determine clinical improvement in NYHA III and IV heart failure. Key words: ST2, heart failure, NYHA III and IV